Ethnobotany plants as traditional food additives in buffalo curry in pasar terandam village, barus district, central tapanuli regency - Erwina Simanullang; Moralita Chatri; Resti Fevria; Des M. M. (Bioscience, 2021)
People in Pasar Terandam Village still use plants as food additives. However, research has never been carried out, so that it has not been recorded and has not been listed. If not inventoried and cultivated, the plant can be lost or extinct. This study aims to determine the plants, -plant organs, plant status, and how to use them as traditional food additives in buffalo meat curry in Pasar Terandam Village, Barus District, Central Tapanuli Regency. This research was conducted from April to May 2020 using a survey method through observation and interviews. The results showed that 19 species from 15 families were used by the community of Pasar Terandam Village as traditional food additives to buffalo meat curry. Parts of plant organs used are tubers, leaves, stems, seeds, fruits, skins, and rhizomes. These plants is processed by cooking, pulverizing / mashed, pounded, cut, shredded, roasted and boiled. The community obtains these plants by cultivating seven species around the house or in the garden and buying them in markets or stalls for 12 species.Masyarakat di Desa Pasar Terandam masih banyak menggunakan tumbuhan sebagai bahan tambahan pangan. Namun, belum pernah dilakukan penelitian sehingga belum terdata dan belum terinventaris. Kalau tidak diinventaris dan dibudidayakan maka tumbuhan itu bisa hilang atau punah. Penelitian ini bertujuan untuk mengetahui jenis-jenis tumbuhan yang digunakan, bagian organ tumbuhan, status tumbuhan dan cara pemanfaatannyasebagai bahan tambahan pangan tradisional pada gulai kerbau di Desa Pasar Terandam Kecamatan Barus Kabupaten Tapanuli Tengah. Penelitian ini dilakukan pada bulan April sampai Mei 2020 menggunakan metode survei melalui observasi dan wawancara.Hasil penelitian didapatkan 19 species dari 15 familia yang digunakan masyarakat Desa Pasar Terandam sebagai tambahan pangan tradsional pada gulai kerbau. Bagian organ tumbuhan yang digunakan adalah umbi, daun, batang, biji, buah, kulit, dan rimpang. Cara penggunaanya yaitu dengan dimasak, diuleg/dihaluskan, ditumbuk, dipotong, diparut, disangrai dan direbus.Masyarakat memperoleh tumbuhan tersebut dengan cara membudidayakan di sekitar rumah atau di kebun sebanyak 7 specises dan membelinya di pasar atau warung sebanyak 12 species.